2015
DOI: 10.2196/resprot.4621
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media While Waiting in Pain: A Clinical 12-Week Longitudinal Pilot Study

Abstract: BackgroundChronic pain places an enormous burden on health care systems. Multidisciplinary pain management services are well documented as an effective means to improve patient outcomes. However, waiting lists to access these services are long and outcomes deteriorate. Innovative solutions such as social media are gaining attention as a way to decrease this burden and improve outcomes. It is a challenge to design research that demonstrates whether social media are acceptable to patients and clinically effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
1
6
0
1
Order By: Relevance
“…For example, education and self-management resources could be offered by primary care providers to improve management of the disease in its early stage. The use of online support groups, pain management videos, blogs [ 49 ] or eConsult services [ 50 ], as well as facilitating communication between family physicians and pain specialists, could improve pain treatment for patients with rheumatic conditions. In addition, the large number of patients referred to MPTF for osteoarthritis or fibromyalgia conditions suggests that primary care failed to effectively manage these patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, education and self-management resources could be offered by primary care providers to improve management of the disease in its early stage. The use of online support groups, pain management videos, blogs [ 49 ] or eConsult services [ 50 ], as well as facilitating communication between family physicians and pain specialists, could improve pain treatment for patients with rheumatic conditions. In addition, the large number of patients referred to MPTF for osteoarthritis or fibromyalgia conditions suggests that primary care failed to effectively manage these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Upon deeper analysis of our survey and pilot study, we were also able to see how those affordances were statistically correlated with good health outcomes [35]. We found that several outcomes were having significantly positive effects, in the social, psychological and cognitive dimensions of the chronic patients' health [36].…”
Section: Therapeutic Affordances Of Social Mediamentioning
confidence: 88%
“…Secondly, we conducted a global online survey using PROMIS (Patient Reported Outcome's Management Information System) [33] as a way to measure beneficial outcomes from those interventions from the perspective of the patient, using a standardised set of questionnaires [34,35]. Finally, we carried out a pilot clinical study in people with chronic pain to evaluate how using social media was improving their health [36].…”
Section: Therapeutic Affordances Of Social Mediamentioning
confidence: 99%
“…They are arguably the best-known example of the way in which digital healthcare has shaped the participatory health paradigm. They are being used to support healthcare delivery 6 , health information search and delivery 6 7 , connection with like-minded individuals, and sharing and crowdsourcing experiences 5 6 8 9 , or promotion of healthy behaviors 10 11 .…”
Section: Introductionmentioning
confidence: 99%